Hubungan Antara Fear Of Missing Out (FOMO) Dengan Kecanduan Media Sosial Pada Remaja Pengguna Media Sosial - Ayu Pratiwi; Anggita Fazriani (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSTRACT Fear of missing out (FOMO) can be known if someone experiences extreme feelings such as, loss, discomfort, stress, irritability, anxiety, and inability far from a smartphone to immediately access it on social media. The purpose of this study was to determine the tendency, adolescents' knowledge was detected by Fear of Missing Out (FOMO) on teenagers using Facebook social media at SMAN 14, Tangerang Regency. The research method used is descriptive correlation with cross sectional approach. The population of 168 respondents with data collection techniques is random sampling by distributing questionnaire sheets that have been valid and reliable. Univariate and bivariate data analysis using Chi-Square and Correlation. Research Results Based on the Chi Square test results obtained P Value 0,000 (<alpha = 0.05) using alpha 5% (0.05) it can be concluded that Ho which means there is a relationship between Fear of Missing Out (FOMO) and addiction social media. Conclusions and Suggestions Based on the results of research on the existence of a significant relationship between Fear of Missing Out (FOMO) with social media addiction in social media users in SMA Negeri 14 Tangerang Regency in 2019. It is recommended that adolescents limit excessive use of social media and increase positive activities in their environment .